Characterization of the mechanical behavior of SU-8 at microscale by viscoelastic analysis. (23rd August 2016) - Xu, Tingge; Yoo, Jun Hyeon; Babu, Sachin; Roy, Samit; Lee, Jeong-Bong; Lu, Hongbing
Abstract: The mechanical properties of SU-8 at microscale were measured under both micropillar compression and nanoindentation on a film on a substrate. To the best of our knowledge, this paper reports the first set of results for microcompression of SU-8 micropillars for measurement of mechanical properties using viscoelastic analysis. The effects of loading rate and micropillar size are examined. It was determined that the SU-8 exhibits viscoelastic properties at room temperature, the time-average Young's modulus increases in general with the loading rate. The average Young's modulus determined by compression of a micropillar was 4.1 GPa at a strain rate near 10 −3 s −1 . For nanoindentation on a SU-8 film supported by a silicon substrate, the default output from the nanoindenter for the Young's modulus was approximately 6.0 GPa with the consideration of elastic–plastic behavior of the SU-8. When the viscoelastic effects were considered, the time-average Young's modulus at a given strain rate was determined to be near 3.6 GPa, which agrees with the reported values in the literature obtained from tension and bending, and also correlates reasonably well with data from microcompression. This work indicates that viscoelastic analysis is necessary to extract the valid mechanical properties at nano/microscales for SU-8.